Pedagogy - Challenges, Recent Advances, New Perspectives, and Applications - Hülya Şenol (IntechOpen, 2022)
Developments in the field of technology along with the Covid-19 pandemic have caused many significant changes and transformations in this century. As such, countries need individuals equipped with 21st-century skills. This requires schools to consider the challenges faced by both students and teachers and develop educational programs to train qualified individuals who can respond to the developments in this century and the future. This book discusses the challenges, advances, and applications in the professional development of teachers and other educators at all academic levels.